2005
DOI: 10.1007/s00464-004-9116-2
|View full text |Cite
|
Sign up to set email alerts
|

Gallbladder cancer presenting with acute cholecystitis: a population-based study

Abstract: In the ethnic Chinese population of Hong Kong, the incidence of gallbladder cancer presenting with acute cholecystitis is higher than the same finding in patients undergoing elective cholecystectomy for cholelithiasis. Long-term survival is possible because such patients may be diagnosed at an early stage of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 8 publications
1
36
1
1
Order By: Relevance
“…The risk of gallbladder cancer is approximately 4-5 times higher in patients with gallstones than without gallstones, especially in susceptible populations such as the natives of South and North America and the Maori population of New Zealand [123]. A retrospective analysis by Lam and coworkers [124] concluded an increase in gallbladder cancer presenting with acute cholecystitis to be higher when compared with the same finding in patients undergoing elective cholecystectomy for cholelithiasis. Not only can an untreated case of cholelithiasis present clinically with the recurrence of the same symptoms, leading to chronic cholecystitis, but it can also lead to a variety of other complications, the most common being acute cholecystitis, acute pancreatitis, ascending cholangitis, and gangrenous gallbladder [125].…”
Section: Complicationsmentioning
confidence: 96%
“…The risk of gallbladder cancer is approximately 4-5 times higher in patients with gallstones than without gallstones, especially in susceptible populations such as the natives of South and North America and the Maori population of New Zealand [123]. A retrospective analysis by Lam and coworkers [124] concluded an increase in gallbladder cancer presenting with acute cholecystitis to be higher when compared with the same finding in patients undergoing elective cholecystectomy for cholelithiasis. Not only can an untreated case of cholelithiasis present clinically with the recurrence of the same symptoms, leading to chronic cholecystitis, but it can also lead to a variety of other complications, the most common being acute cholecystitis, acute pancreatitis, ascending cholangitis, and gangrenous gallbladder [125].…”
Section: Complicationsmentioning
confidence: 96%
“…Currently, there are more studies that have began to focus on UGC [24,25] , but early diagnosis of gallbladder carcinoma is still difficult [26][27][28][29][30] . In order to improve the diagnosis of gallbladder carcinoma, epidemiological and clinicopathological studies should be conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (2012) observed that early diagnosis and timely radical surgery are directly correlated to the prognosis of the patients. Incidental detection of gall bladder cancer in cholecystectomy specimen do has been reported in 0.3-2% of all cholecystectomy performed for benign conditions (Lam et al, 2005;Sun et al 2005;Misra et al, 2006).…”
Section: Introductionmentioning
confidence: 99%